2018
DOI: 10.3389/fmicb.2018.02979
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Evolution of Glucosyltransferase (Gtf) Genes in Streptococcus

Abstract: In many caries-promoting Streptococcus species, glucosyltransferases (Gtfs) are recognized as key enzymes contributing to the modification of biofilm structures, disruption of homeostasis of healthy microbiota community and induction of caries development. It is therefore of great interest to investigate how Gtf genes have evolved in Streptococcus. In this study, we conducted a comprehensive survey of Gtf genes among 872 streptococci genomes of 37 species and identified Gtf genes from 364 genomes of 18 species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…The complete genome of S. oriscaviae HKU75 T identified in this study contained homologs of several virulence genes found in streptococci ( Table 3 ). Examples of these genes include glucosyltransferases ( gtfA ), fibronectin-binding protein ( pavA ), collagen-binding protein ( cpbA ), laminin-binding protein ( lmb ) and enolase ( eno ); these genes are known to be involved in adhesion, colonization, internalization, or invasion ( 19 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…The complete genome of S. oriscaviae HKU75 T identified in this study contained homologs of several virulence genes found in streptococci ( Table 3 ). Examples of these genes include glucosyltransferases ( gtfA ), fibronectin-binding protein ( pavA ), collagen-binding protein ( cpbA ), laminin-binding protein ( lmb ) and enolase ( eno ); these genes are known to be involved in adhesion, colonization, internalization, or invasion ( 19 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…To further address if PcsB expression influences the strain capacity to bind sucrose-derived EPS, we selected strains with the highest ( n = 4; strains SK569, SK579, SK616, SK1073) and lowest ( n = 4; strains SK575, 38–4, 35–15, 26–2) levels of PcsB (produced under aerobic conditions) to compare bacterial aggregation mediated by sucrose-derived EPS. Of note, different from S. mutans , S. mitis does not secrete glucosyltransferase enzymes (Gtfs) required for the synthesis of insoluble glucan EPS from sucrose (Xu et al, 2018). Therefore, to supply S. mitis cultures with sucrose-derived EPS, S. mitis aggregation was assessed in filter-sterilized BHI culture supernatants of S. mutans MT8148 (which contain secreted Gtfs: GtfB, GtfC and GtfD) supplemented with sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…These enzymes retain activity once bound to the surface of bacterial species that typically co-habit dental biofilms (Bowen and Koo, 2011). Different from S. mutans and other streptococcal species of dental biofilms, the genomes of S. mitis strains do not harbor genes encoding Gtfs (Xu et al, 2018). This is consistent with the reduced S. mitis aggregation observed in BHI supplemented with sucrose, a phenotype also reported in S. mutans gtfBCD isogenic mutants (Alves et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…GtfD predominantly synthesizes water soluble glucans 36 . Reports have demonstrated that Gtfs are recognized as pivotal contributors for the alteration of biofilm architecture, disruption of homeostasis in the community of healthy microbiota and induction of caries progression 37 . Ren et al, in 2016 have pronounced that molecules that target the glycosyltransferase possess the ability to inhibit biofilm formation and cariogenicity of S. mutans 38 .…”
Section: Discussionmentioning
confidence: 99%